Commentaires à propos de la loi française sur le harcèlement moral au travail - Marie-France Hirigoyen; Claire Bonafons (Perspectives Interdisciplinaires sur le Travail et la Santé)
The authors will show how in France, starting with a simple description of the suffering caused by harassment, a law punishing this wrong was quickly arrived at. They will then summarize the jurisprudence and the evolution of the behaviours resulting from this law, and finally, they will propose research orientations and possibilities for improving the existing legislation.